2012
DOI: 10.2337/dc12-1128
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Phase Ib Study of Ghrelin Agonist, RM-131, in Type 2 Diabetic Women With Delayed Gastric Emptying

Abstract: OBJECTIVETo investigate the pharmacokinetics (PK), pharmacodynamics, and safety of single-dose RM-131 in type 2 diabetic patients with gastrointestinal cardinal symptoms (GCSI) and previously documented delayed gastric emptying (DGE).RESEARCH DESIGN AND METHODSIn a randomized crossover study, 10 female patients received RM-131 (100 μg s.c.) or placebo and underwent scintigraphic gastric emptying (GE) and colonic filling at 6 h (CF6) of a solid-liquid meal administered 30 min postdosing. Adverse events, plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 41 publications
5
93
0
2
Order By: Relevance
“…This observation highlights the unresolved question of whether the low-fat, EggBeaters meal is even the optimal solid meal substrate; indeed, significantly different emptying between the EggBeaters meal and a radiolabeled liver at 3 h was reported in the original report ''validating'' the EggBeaters meal [1]. GES also has utility in the evaluation of the motility effects of drugs, such as has been reported for studies utilizing the 2 % fat EggBeaters meal [7,8] and with the higher-calorie (296 kcal) and 32 % fat scrambled eggs meal [9,10].…”
mentioning
confidence: 95%
“…This observation highlights the unresolved question of whether the low-fat, EggBeaters meal is even the optimal solid meal substrate; indeed, significantly different emptying between the EggBeaters meal and a radiolabeled liver at 3 h was reported in the original report ''validating'' the EggBeaters meal [1]. GES also has utility in the evaluation of the motility effects of drugs, such as has been reported for studies utilizing the 2 % fat EggBeaters meal [7,8] and with the higher-calorie (296 kcal) and 32 % fat scrambled eggs meal [9,10].…”
mentioning
confidence: 95%
“…Improvements in in GE Tlag, GE T1/2 liquids, and colonic filling at 6 hours were observed, although not statistically significant. No significant effects was observed for total GCSI-DD score or composite scores for nausea, bloating postprandial fullness and pain; however, the study was not powered for these endpoints and baseline symptom severity was not a criterion for study eligibility [86].…”
Section: Current Clinical Trials Of Ghrelin Agonists In Gastroparesismentioning
confidence: 99%
“…In pre-clinical studies prior to acquisition of RM-131 by Rhythm Pharmaceuticals, RM-131 has been shown to cause a dose-dependent increase in food intake and weight gain (both fat and lean mass) with greater potency than human ghrelin [85]. In a rat models, RM-131 was successful in reversing postsurgical, opiate-induced gastric ileus while in normal, nonsurgical primates, RM-131 increased the GE rate [86]. RM-131 also displayed anti-inflammatory effects and increased survival in models of inflammatory bowel disease.…”
Section: Current Clinical Trials Of Ghrelin Agonists In Gastroparesismentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Moreover, RM-131 exerts improved stability, greater potency, and longer plasma half-life. 36,38 RM-131 may be used in the treatment of gastroparesis, since in gastroparesis RM-131 accelerates gastric emptying without causing severe adverse effects.…”
Section: Relamorelinmentioning
confidence: 99%